The best lawyer in a one-lawyer town : a memoir - Bumpers, Dale (University of Arkansas Press, 2004)
If Frank McCourt had grown up in Depression-era Arkansas, he might write like Dale Bumpers, one of the most colorful, entertaining, and wise politicians in recent American history, Atticus Finch with a sense of humor. In The Best Lawyer in a One-Lawyer Town, Bumpers tells the story of his remarkable journey from poverty to political legend, and the result is a great American memoir that has attracted wide acclaim for its clever southern charm.